2021
DOI: 10.32598/ppj.25.2.30
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective effects of hydroethanolic extracts of Crocus sativus tepals, stigmas and leaves on carbon tetrachloride induced acute liver injury in rats

Abstract: Introduction: The present study investigated the hepatoprotective effects of stigmas, tepals and leaves of Crocus sativus on carbon tetrachloride (CCL4) induced liver injury in rats. Methods: Hydroethanolic extracts of Crocus sativus (stigmas, tepals and leaves) were administrated daily for 14 days by oral gavage. In the present study, 30 male rats divided into five groups were treated as 1: normal rats gavaged with distilled water; 2: intoxicated rats gavaged with distilled water and injected with CCL4; 3: ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…Preparation of the plant material was done using the technique outlined by Ouahhoud et al [ 8 ]. First, the stigmas and various C. sativus components were manually separated.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Preparation of the plant material was done using the technique outlined by Ouahhoud et al [ 8 ]. First, the stigmas and various C. sativus components were manually separated.…”
Section: Methodsmentioning
confidence: 99%
“…According to our early research, 80% ethanol was the solvent with the best biological characteristics [ 6 , 8 ]. The Ouahhoud et al [ 6 ] procedure is the one that is in use for this study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, C. sativus is only valued by its stigmas and much of the saffron byproducts such as tepals and stamens are not used and are usually discarded during stigma development (Sánchez-Vioque et al 2012a). Recently, some pharmacological studies have been suggested the medicinal values of saffron tepals extract and found hepatoprotective (Ouahhoud et al 2021;Omidi et al 2014), antidepressant (Akhondzadeh Basti et al 2007), anti-oxidant (Sánchez-Vioque et al 2012bWali et al 2020), and antifungal (Khoulati et al 2019) properties. Till now the medicinal properties of stamens is poorly studied.…”
Section: Introductionmentioning
confidence: 99%